2002
DOI: 10.1523/jneurosci.22-13-05572.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Learning and Memory and Altered GABAergic Synaptic Transmission in Mice Lacking the α5 Subunit of the GABAAReceptor

Abstract: The alpha5 subunit of the GABA(A) receptor is localized mainly to the hippocampus of the mammalian brain. The significance of this rather distinct localization and the function of alpha5-containing GABA(A) receptors has been explored by targeted disruption of the alpha5 gene in mice. The alpha5 -/- mice showed a significantly improved performance in a water maze model of spatial learning, whereas the performance in non-hippocampal-dependent learning and in anxiety tasks were unaltered in comparison with wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
436
4
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 578 publications
(478 citation statements)
references
References 45 publications
35
436
4
3
Order By: Relevance
“…In fact, mutant mice lacking the a5 subunit of the GABA A receptor, which is important for tonic inhibition (see above), showed enhanced learning and memory. 47 The idea that activin, by reducing GABA tonus, would also improve cognitive performance is particularly intriguing in light of our previous study on the role of activin in excitatory neurotransmission. There, we reported that activin augments NMDA receptor currents and promotes hippocampal LTP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mutant mice lacking the a5 subunit of the GABA A receptor, which is important for tonic inhibition (see above), showed enhanced learning and memory. 47 The idea that activin, by reducing GABA tonus, would also improve cognitive performance is particularly intriguing in light of our previous study on the role of activin in excitatory neurotransmission. There, we reported that activin augments NMDA receptor currents and promotes hippocampal LTP.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, all three newly synthesized BZ site ligands could have acted through the a 5 subtype-containing GABA A receptors, one of them (SH-053-R-CH3) as an essentially subtype-selective ligand. There exist data that support the possibility of substantial motor manifestations of a5-containing GABA A receptor modulation, besides the indirect consequences brought on by the effects on learning and memory processes, where pertinent (Collinson et al, 2002;Crestani et al, 2002). Somatic and preganglionic motoneurons in the spinal cord exhibit a moderate-to-strong staining for the a5 subunit (Bohlhalter et al, 1996), whereas the knock-in mice harboring the a5 subunit insensitive to diazepam are refractory to development of tolerance to the sedative effect of diazepam dosed subchronically, presumably due to a downregulation of a5 subunits in the dentate gyrus (van Rijnsoever et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Knock-in mice with the GABA A receptor a5 subunit rendered insensitive to diazepam were refractory to development of tolerance to the sedative effect of diazepam dosed subchronically (van Rijnsoever et al, 2004). These two sets of evidence indicate that the motor influence of a5-GABA A receptor modulation, if present, is not necessarily an indirect consequence of the established effects on learning and memory processes (Collinson et al, 2002;Crestani et al, 2002). Hence, any activity changes seen with ligands possessing a substantial agonistic efficacy for a5 subunit containing GABA A receptors may be, at least partly, mediated by such receptors.…”
Section: Introductionmentioning
confidence: 91%
“…These receptors are known regulators of neurogenesis (50). RA is also known to induce differentiation of several neuronal progenitors toward a phenotype of GABAA receptor expression (51,52), and these receptors are essential for hippocampal-mediated cognitive function via regulation of synaptic transmission (53). A third mechanism may be proposed based on the influence of RA on hippocampal long-term potentiation and long-term depression.…”
Section: Discussionmentioning
confidence: 99%